Answer:
b = 40
Step-by-step explanation:
Answer:
mean:-3
median:5
mode: all values appeared once
range:169
Step-by-step explanation:
Answer:6
Step-by-step explanation:
*we solve every bracket alone
-(√2+1)² = [rule:1st *1st + 2*1st*2nd + 2nd*2nd]
2+2√2+1
3+2√2
-(√2-1)= [rule:1st*1st - 2*1st*2nd + 2nd+2nd]
2-2√2+1
3-2√2
-we write the whole equation
3+2√2+3-2√2 (+2√2 - 2√2) {positive and negative remove each other}
3+3=6
11. 8/7
14. 13/10
17. 11/14
Answer:
(2,-4)
Step-by-step explanation:
-4+2=-2
10+-4=10-4=6